2011
DOI: 10.1007/s10389-011-0437-z
|View full text |Cite
|
Sign up to set email alerts
|

Food safety at home: knowledge and practices of consumers

Abstract: AimTo define food safety and risk perception of foodborne diseases in the private home setting and identify specific behaviours during food purchase, storage and preparation in a large survey study.Subject and methodsA large sample of individuals (n = 1,000) living in the area of Cassino, Italy, volunteered to participate in the study. All participants were randomly recruited and underwent a questionnaire-based interview at their home regarding food-safety measures. Logistic regression analyses were used to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
4
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 24 publications
7
81
4
7
Order By: Relevance
“…The result can imply that single farmers might have lower liquidity constraints in the household, thus may be more likely to pay for aflatoxin control. However, this result contradicts those of Langiano et al (2012) who reported that high-risk behavior of improper safety rules was influenced more by single status than by being married.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The result can imply that single farmers might have lower liquidity constraints in the household, thus may be more likely to pay for aflatoxin control. However, this result contradicts those of Langiano et al (2012) who reported that high-risk behavior of improper safety rules was influenced more by single status than by being married.…”
Section: Discussioncontrasting
confidence: 99%
“…However, this result contradicts those of Langiano et al. () who reported that high‐risk behavior of improper safety rules was influenced more by single status than by being married.…”
Section: Discussioncontrasting
confidence: 99%
“…But there are gaps in consumer applications of Clean, Separate, Chill, and Cook advice from the Dietary Guidelines for Americans and food safety programs like Fight Bac! and the World Health Organization’s Five Keys to Safer Food [22,41,58,59,60,61,62,63,64,65,66], that have been documented in the U.S., Australia, Ireland, Italy, Slovenia, and Turkey [15,67,68,69,70]. Inconsistent practices among home food handlers can negate much of the effort made in improving and maintaining food safety achieved earlier in the food chain [15,52].…”
Section: What Are Consumers Doing With Regard To Food Safety?mentioning
confidence: 99%
“…A number of studies in the United Kingdom, the United States, Europe, and New Zealand have demonstrated that many consumers have inadequate food safety knowledge. This includes knowledge of appropriate cooling and storage of cooked foods, safe preparation of meat and vegetables, adequate hand washing, correct refrigerator temperature, cleansing of food prepara tion surfaces, and awareness of the pathogens which can cause food poisoning (3,14,(23)(24)(25).…”
mentioning
confidence: 99%